PROBLEM QUESTIONS OF QUALITATIVE EDUCATION OF PEDIATRICIANS - L.V. Erman; A.A. Baranov; A.S. Simakhodskiy; N.P. Shabalov (Вопросы современной педиатрии, 2009)
Authors of the article put questions of qualitative higher education of pediatricians, necessity of addition of practical work hours in pediatric and maternity care institutions. Also the article describes the ways of skills acquisition corresponding to the tasks of priority national project «Health» with future specialists.Key words: children, education, pediatricians, national project «Health».(Voprosy sovremennoi pediatrii — Current Pediatrics. 2009;8(3):5-9)